2001
DOI: 10.1111/1467-8683.00258
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of Board Leadership Structure and Financial Performance: are “two heads better than one”?

Abstract: Given conflicting theoretical perspectives and inconsistent empirical results, this study examined the relationship between board leadership structure and organisational performance. A meta-analysis based on 22 independent samples across 5,751 companies indicates that independent leadership structure has a significant influence on performance. This relationship varies depending upon the context of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 19 publications
12
104
0
2
Order By: Relevance
“…Using 25 Canadian firms from 1976 to 2000, Bozec (2005) reports that CEO duality has no impact on market valuation. This is consistent with the results of previous studies (Baliga et al, 1996;Brickley et al, 1997;Rhoades et al, 2001;Vafeas and Theodorou, 1998;Laing and Weir, 1999;Weir and Laing, 2000;Sanda et al, 2010), which suggest that CEO duality has no impact on market valuation.…”
Section: The Theoretical and Empirical Literature On Dbls And Market supporting
confidence: 93%
“…Using 25 Canadian firms from 1976 to 2000, Bozec (2005) reports that CEO duality has no impact on market valuation. This is consistent with the results of previous studies (Baliga et al, 1996;Brickley et al, 1997;Rhoades et al, 2001;Vafeas and Theodorou, 1998;Laing and Weir, 1999;Weir and Laing, 2000;Sanda et al, 2010), which suggest that CEO duality has no impact on market valuation.…”
Section: The Theoretical and Empirical Literature On Dbls And Market supporting
confidence: 93%
“…However, the results of the previous studies are inconsistent. Some of the previous studies found that better firm performance is related to good CG (Baysinger& Butler,1985;Brickley&James, 1987;Rechner& Dalton, 1991;Byrd &Hickman, 1992;Brickley et al, 1994;Rhoades et al, 2001;Coles &Jarrell, 2001;Haniffa&Hudaib, 2006) and some other studies found a negative relationship between CG and firm performance (Bathala&Rao, 1995;Kien, Suchard&Jason, 2004;Hutchinson, 2002;Ertugrul&Hegde;2004). Besides, some other studies could not find any significant relationship between CG and firm performance (Prevost et al 2002;Park &Shin, 2003;Singh &&Davidson, 2003).…”
Section: Problem Statementmentioning
confidence: 95%
“…The variables considered in this study (board size, board composition, duality, promoter shareholding) have been found to have some impact on the financial performance of a firm which has been measured based on return on assets, return on equity and Tobin's q in various research papers (Ibrahim & Samad, 2014;Kiel & Nicholson 2003;and Rhoades et al, 2001). However, the relevance of audit committee characteristics has not been investigated much.…”
Section: Literature Reviewmentioning
confidence: 99%